2006
DOI: 10.1111/j.0022-4146.2006.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects Of Impact Fees On Multifamily Housing Construction*

Abstract: Development impact fees may create more housing opportunities for lowerincome households within suburban areas if there is a fiscal incentive behind the adoption of exclusionary land-use regulations. Using panel data estimation techniques that allow us to control for unobservable heterogeneity and potential endogeneities, we estimate the effects of different types of impact fees on multifamily housing construction using data from Florida counties. Impact fees earmarked for public services other than for offsit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…7 These regulations increase the developer's costs of obtaining project approval. 8 For example, if single-family housing is seen as a free rider, less land may be zoned for single-family homes, increasing the likelihood that the developer must obtain a rezoning in order to build. Rezonings lengthen the project review process and increase the developer's compliance costs.…”
Section: Impact Fees and Single-family Home Constructionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 These regulations increase the developer's costs of obtaining project approval. 8 For example, if single-family housing is seen as a free rider, less land may be zoned for single-family homes, increasing the likelihood that the developer must obtain a rezoning in order to build. Rezonings lengthen the project review process and increase the developer's compliance costs.…”
Section: Impact Fees and Single-family Home Constructionmentioning
confidence: 99%
“…See Ihlanfeldt [15] for a review of the evidence on various forms of exclusionary land-use regulation. 8 We assume the residential land developer is also the homebuilder. Separating land development from homebuilding complicates the model without altering its main conclusions.…”
Section: Impact Fees and Single-family Home Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…18. For example, Burge and Ihlanfeldt (2006) investigate the effect of impact fees (to finance public infrastructure) on the construction of new homes, drawing on data from Florida. They found that impact fees earmarked for public services other than water and sewer system improvements increased the construction of small homes within inner suburban areas and of medium and large homes within all suburban areas.…”
Section: Notesmentioning
confidence: 99%
“…On the empirical side, Skidmore and Peddle (1998) find that residential development in DuPage County IL fell substantially after the imposition of an impact fee. By contrast, Ihlanfeldt (2006a and2006b) develop a model to show that impact fees can boost construction by substituting for exclusionary regulations and decreasing uncertainty about project approval. In a panel of counties in Florida, they document a positive relationship between construction of most types of suburban single-35 He finds a smaller effect of regulation on house prices when regulation is assumed to be exogenous, which is somewhat puzzling since most theories would suggest that regulation should be stronger in high-priced areas, biasing the estimated effect using OLS upwards.…”
mentioning
confidence: 99%